(untitled) (Szociológiai Szemle, 2024)
Based on the data of the 1992 wave of the Hungarian Household Panel, prepared by the Budapest University of Economics and the Informatics Association of Social Sciences, the paper tries to find an answer to the question what factors determine satisfaction with living standards after the systemic change. The actual financial situation and the income are less decisive. Though a bigger income and better financial conditions result in bigger satisfaction, yet the extent of satisfaction does not follow the pace of the rate of income indices. Subjective opinion, psychological attitudes — particularly the career covered and the image of the future — influence the sense of satisfaction to a far greater extent than the financial conditions and incomes. After the systemic change partly there is relative satisfaction in the Hungarian society, and partly there is relative deprivation, but in different proportions in each stratum, yet the proportion of those who are satisfied, who pull towards the centre and the dissatisfied is significant. Those middle strata which are sliding down, who lose their income position, are not increasingly dissatisfied. The authors draw the conclusion that the satisfied elements of the middle strata choose those to be their reference group who are already in a deprived situation.